Libres propos conclusifs sur la dette écologique - Alexandra Langlais (Éditions en environnement VertigO, 2016)
The ecological debt helps improving the understanding of our relationship with nature. The concept considers the past in order to think the present and imagine the future. It also highlights yet another facet of our responsibility for people and nature. Namely, the notion of debt finds its meaning in the logic of sharing, and maybe be defined as a fair distribution and re-distribution of natural resources. We must also consider the complementarity of the concept of ecological debt with those of sustainable development and ecological solidarity. The ecological debt can thus not be reduced to a simple economic reading. Operationally, the concept of ecological debt resonates with that of payments for environmental services. The related questions are common: how to calculate debt or payement? Who is the debtor and who is a creditor? In order to consider the terms of refund of the debt within the logic of solidarity, we must consider the permanent link between the duty of solidarity and the right to enjoy the benefits of nature.